Pemenuhan Hak Anak Terhadap Korban Eksploitasi Oleh Orang Tua di Yayasan Anak Bangsa Malang (RechtJiva, 2025)
Economic exploitation of children who are employed is the act of using children unreasonably and excessively to work for the benefit of other parties, including parents or employers, which ignores the safety, health and basic rights of children. According to Law Number 35 of 2014 concerning Child Protection, economic exploitation is strictly prohibited because it threatens children's growth and development and hinders children's rights to education, playing and living in a safe environment. Based on these problems, the author conducted research with the problem formulation: 1.) What is the role of the Malang City Children's Social Foundation in providing legal protection for child workers in Malang City? 2.) What is the strategy of the Malang City Children's Social Foundation in overcoming the obstacles faced in assisting child workers in Malang City? The type of research method is empirical research, using a sociological juridical approach. The research location is in the Malang area. From the research results, the author obtained data that 6 (six) children experienced economic exploitation and were being assisted by the with children social Malang  Foundation has an important role in providing protection and legal assistance for child workers in Malang City. This foundation carries out various efforts such as providing legal assistance, counseling to parents, increasing public awareness, and providing moral and material support to children who are forced to work.There is still a need for stricter law enforcement and increased public awareness to overcome the problem of child labor in Malang City.